Additions to the Inocybe sect. Leptocybe (Agaricales) in China: new species from tropical rainforests, new geographical distributions, and toxin detection - Gao, Jia-Long; Wu, Xiao-Peng; Zhou, Yu-Ling; Yu, Wen-Jie; Fan, Yu-Guang (Frontiers in Microbiology, 2025)
Inocybe is a cosmopolitan genus of ectomycorrhizal fungi within the family Inocybaceae. Members of this genus are recognized as a group of toxic mushrooms linked to poisoning incidents worldwide. Clarifying this species diversity and toxin profiles within this genus is critical for both taxonomy and public health. In this study, we describe two newly identified species, I. bicystidiata sp. nov. and I. microcarpa sp. nov., based on phylogenetic analysis and morphological evidence. Phylogenetically, the two new species belong to I. sect. Leptocybe. Inocybe bicystidiata is characterized by nodulose basidiospores with saddle-shaped projections and the coexistence of thick-walled pleurocystidia and thin-walled paracystidia on the lamellar side. Inocybe microcarpa is characterized by very small basidiomata, spinose basidiospores with forked projections, absence of pleurocystidia, and thin-walled cheilocystidia. Ecologically, both of these new species occur in tropical rainforests dominated by Parashorea chinensis, which is considered as their presumed host. In addition, new geographic data are reported for three previously documented species of I. sect. Leptocybe, I. acutata, I. juji, and I. peppa, based on newly obtained specimens. Comprehensive ultra-performance liquid chromatography-mass spectrometry (UPLC–MS)/MS toxin screening revealed no detectable levels of muscarine, psilocybin, psilocin, bufotenine, or baeocystin in 10 examined species of sect. Leptocybe. This contrasts with the known toxin-producing Inocybe lineages, suggesting a divergent secondary metabolism in this clade.